Somatic Embryogenesis and Regeneration in Chinese King Grass (Pennisetum Purpureum cv.) - Younas, Sadaf; Khanum, Plosha; Waheed, Ummara; Rashid, Muhammad Zahid; Bokhari, Anum Masood; Amina; Muhammad, Rao Wali; Rashid, Minahil; Zahra, Fatima TU (Journal of Agriculture and Biology, 2025)
The demand for animal product is quickly expanding in Pakistan, due to increasing population which result in shortage of animal feed. Animal nutrition deficiency had negative impact on livestock productivity and production. Improving farm animal productivity is one of the major challenge nowadays. Therefore, we need to increase crop productivity by cultivating high yielding fodder varieties. King grass (Pennisetum purpureum cv.) belongs to family Poaceae. The shape is almost similar to sugar cane and very high in nutritional value. Freshly chopped king grass can be utilized as animal feed, hay, silage or feed pellets but serious problems such as pests and diseases, non-availability of good seed material affecting its nutritional value. Therefore, tissue culture technique provides an alternative method for producing disease-free and high-quality plant material at large scale. An efficient embryogenic callus of king grass was obtained which was further capable of plant regeneration. The MS medium combined with (MS + 2,4-D 4.0 mg/L) produced the best callus response in which callus was creamy yellow and nodular in shape and took minimum days for callus induction. The result shows that the king grass's new inner whorl of leaves and shoot apical meristem were very responsive to in-vitro somatic embryogenesis and plant regeneration by using hormones such as  (BAP),  (KIN), (IAA), (2 ,4- D) or  (NAA). Regeneration under MS + BAP (1.5 mgL-1) was the best. The minimum days for rooting were taken by using MS + I A A (0. 5 m g L-1) + N A A (1 .5 m g L-1). While MS medium with BAP and NAA showed best response for shooting and rooting. In this study different parameters such as days taken to callus formation, callus color, shape, days taken to plant regeneration, shoot formation and root formation was observed. The study achieved efficient plant regeneration, shoot formation, and root formation, providing a viable method for large-scale production of high-quality King Grass for animal feed.
Keywords: Embryogenic callus; plant regeneration; plant growth regulators; morphogenic response.